(untitled) (Revista Nacional de Odontología, 2015)
Introduction: a parafunctional habit is the result of the perversion of a regular function acquired by the repeated practice of a non-necessary action in the oral cavity. The goal of this study was to evaluate the frequency of parafunctional habits in a group of students from the Municipality of Nezahualcoyotl, State of Mexico. Methods: an observational descriptive cross sectional study was carried out in 300 children from 6 to 11 years old. The epidemiologic survey was developed in two times: the first one consisted in the application of a questionnaire to the parents and the second one, an oral examination to the students. For this purposes an examiner (kappa = 0.892) was standardized. Results: at least 34.7% of the analyzed students presented a parafunctional oral habit, being the most frequent in the ages from 6 to 7, showing no relevant differences regarding gender. Nail biting and buccal breathing were the most frequent habits (20.7% and 15.7%, respectively). Conclusions: the frequency of parafunctional habits was low, and it was not associated to age or gender.